Dr. Hani Rayess — Deep Plane Facelift — Tampa - Rayess, Hani (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Hani Rayess, practicing in Tampa, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003056; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; tampa